1999
DOI: 10.1677/joe.0.1630255
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thymulin on spontaneous puberty and gonadotrophin-induced ovulation in prepubertal normal and hypothymic mice

Abstract: The effects of thymulin administration beginning on days 19 or 24 of age on spontaneous puberty and gonadotrophin-induced ovulation were analysed in female normal and hypothymic mice. In normal and hypothymic mice, the daily administration of thymulin at 24 days of age resulted in a delay in the age of vaginal opening, with an increase in serum progesterone levels. Normal mice treated with 200 ng thymulin beginning on day 19 of age and injected with pregnant mare serum gonadotrophin (PMSG) 24 h later had an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
(21 reference statements)
0
15
0
1
Order By: Relevance
“…According to Brown et al [27] , thymulin stimulates the release of follicle-stimulating hormone (FSH) and LH on pituitary cell cultures maintained in dynamic or stationary systems, while Hinojosa et al [4] showed that injecting thymulin subcutaneously into prepubertal mice stimulates the ovulation response induced by equine chorionic gonadotrophin (eCG) treatment.…”
Section: Effects Of Injecting Thymulin Into the Anterior Or Medial Hymentioning
confidence: 99%
“…According to Brown et al [27] , thymulin stimulates the release of follicle-stimulating hormone (FSH) and LH on pituitary cell cultures maintained in dynamic or stationary systems, while Hinojosa et al [4] showed that injecting thymulin subcutaneously into prepubertal mice stimulates the ovulation response induced by equine chorionic gonadotrophin (eCG) treatment.…”
Section: Effects Of Injecting Thymulin Into the Anterior Or Medial Hymentioning
confidence: 99%
“…Based on published results on the effects of neonatal or infantile thymectomy (Besedovsky and Sorkin, 1974;Michael et al, 1980;Kosiewicz and Michael, 1990;García et al, 2000), the congenital absence of the thymus (Rebar et al, 1981b), and the effects of thymic peptides on in vivo and in vitro models (Rebar et al, 1981a;Michael, 1983;Mendoza and Romano, 1989;Mendoza et al, 1995;Hinojosa et al, 1999), the participation of the thymus in regulating the hypothalamic-pituitary-ovary axis is widely accepted.…”
Section: Introductionmentioning
confidence: 99%
“…In both models, grafting the thymus or epithelial thymic cells results in the detection of thymulin in serum (Bach et al, 1977;Dardenne et al, 1984;Safieh et al, 1990). Injecting equine chorionic gonadotropin (eCG) to 20-day old mice does not induce ovulation; however, thymulin treatment before eCG injection results in an increase of both, ovulation rate and ovarian weight (Hinojosa et al, 1999). Infantile thymectomy in mice results in lower serum level of estrogen during the pre-pubertal phase and in a lower ovulatory response to gonadotropin stimulus; in turn, injecting thymulin immediately after surgery resulted in normal estrogen level and normal ovulation rates (García et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Thymulin is a nonapeptide that is produced exclusively by thymic epithelial cells (Dardenne et al 1974, Savino et al 1982, Safieh et al 1990, promotes activation and differentiation of T-cells (Dardenne et al 1974), and stimulates gonadotrophin-induced ovulation in prepubertal mice (Hinojosa et al 1999).…”
Section: Introductionmentioning
confidence: 99%